Pengaruh Bauran Ritel pada Keputusan Pembelian Konsumen dalam Berbelanja di Super Market Mai Mart Kota Bima - Imelda Elizabeth Belseran; Ismunandar Ismunandar; Sri Ernawati (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the influence of retail mix variables on purchasing decisions at Mai Mart Supermarket, Bima City. The sample for this research is between 30 and 500. So the number of samples in this research is 50 people with a Rurposive Sampling sampling technique, namely a data source sampling technique with certain considerations. Considering the limited number of consumers who shop at the Maimart Supermarket in Bima City. The data processing method uses multiple linear regression and the T test. The results of this research state that the Retail Mix variable does not have a significant effect on purchasing decisions at the Mai Mart supermarket in Bima City.